Analisis Resiko Kecelakaan Kerja dengan Metode Job Safety Analysis di PT. Sarana Sampit Mentaya Utama Balikpapan - Ilham Dwi Septya Widodo; Ida Rosanti; Purbawati Purbawati; Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Occupational Health and Safety (OHS) is a systematic effort aimed at protecting workers from the risks of accidents and work-related diseases. The implementation of OHS integrated with risk management helps identify, evaluate, and control potential hazards effectively in the workplace. This study was conducted at PT. Sarana Sampit Mentaya Utama, Balikpapan Branch, a company engaged in asphalt production. The main objectives of this research were to identify potential hazards, determine appropriate control measures, and evaluate the role of the Job Safety Analysis (JSA) method in supporting OHS. The research method used is JSA, which involves identifying each work step, determining the likelihood and severity of risks, and calculating the risk rating to assess the level of risk. The results showed that there are three potential hazards with a medium-risk category, namely in the activities of raw material mixing, quality control, and asphalt distribution. Additionally, three potential hazards with a low-risk category were found in the processes of raw material weighing, raw material transfer, and pump line valve opening. Recommended control measures to reduce risks include the use of appropriate personal protective equipment (PPE) for each task, improving work facilities and infrastructure, and implementing proper load lifting procedures. The application of JSA has proven effective in raising the company's awareness of potential risks in the workplace. This has led to the implementation of better preventive measures, ultimately contributing to the creation of a safer, healthier, and more productive work environment. Therefore, the integration of OHS with risk management at PT. Sarana Sampit Mentaya Utama plays a significant role in safeguarding the safety and well-being of workers.